The Effect of Friends Counseling on Social Interaction of Students of Class XI IPA 5 MAN 3 Medan - Abdurrahman Abdurrahman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2021)
This study aims to determine the effect of peer counseling on the social interaction of students in class XI IPA 5 MAN 3 Medan. This study uses a quasi-experimental method. The sample is 36 students of MAN 3 Medan. Data collection techniques were carried out through the distribution of questionnaires. The data were analyzed using a different test. The results showed that: There is an effect of peer counseling on social interaction of students in class XI IPA 5 MAN 3 Medan with the calculation results obtained by the price tcount ttable = (14.66 > 1.688). Therefore, it can be concluded that peer counseling to improve intrapersonal competence, one of which is the problem of social interaction, is considered feasible to be used as a counseling service that can be modified according to conditions, schools and student problems.